Postoperative "Chimney" for Unintentional Renal Artery Occlusion after EVAR. (13th November 2014) - Franchin, Marco; Fontana, Federico; Piacentino, Filippo; Tozzi, Matteo; Piffaretti, Gabriele
Abstract : Renal artery obstruction during endovascular repair of abdominal aortic aneurysm using standard device is a rare but life-threatening complication and should be recognized and repaired rapidly in order to maintain renal function. Both conventional surgery and endovascular stenting have been reported. We report a case of late postoperative bilateral "chimney" to resolve a bilateral thrombosis of the renal artery following an uncomplicated endovascular aortic repair.